P97 Gastro-oesophageal reflux in cystic fibrosis. (15th November 2016) - Lord, RW; Pearson, JS; Barry, PJ; Whorwell, PJ; Jones, RB; McNamara, P; Beynon, R; Smith, JA; Jones, AM
Abstract : Background: Initial small studies using combined pH and impedance (pH-MII) have suggested increased gastro-oesophageal reflux (GOR) in adult cystic fibrosis (CF) patients. Reflux episodes frequently reach the proximal oesophagus and occur whilst supine, which may predispose to micro-aspiration. Aims: To investigate the relationship between GOR and CF lung disease. Methods: We conducted a prospective observational study in stable adult CF patients undergoing 24 hour pH-MII. Reflux symptoms (using validated RESQ-7 questionnaire) and spirometry were also recorded. Results: 10/12 subjects recruited completed pH-MII the study (mean age 28.5 years, mean FEV1 48.8% predicted, 100% male). An increased number of reflux episodes per 24 hours were noted in 80% of participants (median 104.1, IQR 78.6 –164.4, normal range <75 episodes), with increased 'high-risk' proximal reflux or supine reflux noted in 60% (Table 1 ). In this small preliminary patient sample there were no significant correlations between FEV1% and total, proximal or supine reflux episodes, or RESQ-7 heartburn scores and any reflux measure. 7/10 subjects completed the study on a PPI and had data available for acid reflux (pH < 4) parameters. 4/7 had an abnormal acid exposure despite standard dose PPI therapy. 5/7 had prolonged acid reflux events; the longest was 66.5 minutes (see Table 1 ). Conclusions: In this preliminary data set, CF patients appear to have a pattern of GOR that puts them at risk of reflux micro-aspiration and have significant acid reflux despite antacid therapy. Reflux symptoms and spirometry were not related to reflux parameters. The clinical implications of these findings are that standard PPI dosing maybe insufficient in CF patients to control acid reflux. In addition silent reflux aspiration maybe occurring and as such could be a potential area for future therapies.